DOSAGES ANALYSIS OF HYPERBARIC OXYGEN THERAPY TO IMPROVING COGNITIVE FUNCTION IN PATIENTS POST-TRAUMATIC BRAIN INJURY: A REVIEW - Nuri, Almas; Edi, Djatiwidodo; Anindya, Pramita; Ilmawan, Moh. Fathi (MNJ (Malang Neurology Journal), 2025)
Background: Traumatic brain injury is a type of intracranial injury caused by a mechanical impact that causes anatomical and physiological damage to the brain. Globally, there are 50 million cases of traumatic brain injury each year that cause 10 million deaths and/or hospitalizations. Hyperbaric oxygen therapy is a therapy that uses 100% oxygen at pressures greater than 1 Atmosphere Absolute  (ATA) to increase tissue oxygenation and repair damaged tissue. This study was made to determine the effect of hyperbaric oxygen therapy on improving cognitive function in post-traumatic brain injury patients and the mechanisms underlying it. Objective: To determine the dose of hyperbaric oxygen therapy that can trigger improved cognitive function in post-traumatic brain injury patients, as well as the side effects. Methods: This research is descriptive research and uses the literature study method. In collecting data, using all journals with the search keywords "hyperbaric oxygen therapy" "traumatic brain injury" "hyperbaric oxygen therapy for TBI" "HBOT and TBI" "oxygen therapy and brain injury" published in 2017 - 2022 and indexed by Scimago Journal & Country Rank (SJR) and/or Science And Technology Index (SINTA) then new conclusions and descriptions are made. Results: After selecting 262 journals, ten journals met the inclusion and exclusion criteria. The ten journals stated that there was an effect of hyperbaric oxygen therapy on improving cognitive function in post-traumatic brain injury patients. assessment of improvement in cognitive function in the attached journal, assessed with different parameters. Conclusion: Hyperbaric oxygen therapy is a potential therapy to accelerate cognitive function improvement in post-traumatic brain injury patients.